Social Citizenship through Social Forces: A Case Study of Nepali Women - Maskey, Prapanna (Historical Journal, 2023)
The present paper aims to show a correlation between social forces and social citizenship. The paper highlights the aspect of citizenship rights of Nepali women. Nepali society is composed of people holding different aspirations. If the aspirations of people remain unfulfilled then people adopt the medium of social forces to transform their state. Not only a single force determines to ensure social citizenship but the action of social force plays the determining role. In the Nepali context, common Nepali people were deprived of educational rights and treated as subjects rather than citizens. It is the political movement of 1951 that transformed the social status and role of Nepali people including women. Similarly, social force ensured the democracy of Nepal in 1996. Onward movements of social force the constitution of 1990 declared Nepal as a multi-cultural, multi-lingual, and multi-religious country. The people’s war of Nepal from 1996 to 2006 played an imperative role to ensure the social citizenship of the Nepali people. The interim constitution of Nepal 2006 ensured the inclusion of Women, Dalits, indigenous ethnic groups, Madhesi communities, oppressed groups, poor farmers, and laborers, who are economically, socially, or educationally backward with the right to participate in state structures based on principles of proportional inclusion.